A new sampling method with zirconium‐loaded resin for phosphate oxygen isotope analysis in oligotrophic freshwater systems. (13th September 2022) - Ishida, Takuya; Tayasu, Ichiro; Onodera, Shin‐ichi; Ban, Syuhei; Okuda, Noboru
Abstract : Rationale: The phosphate oxygen isotope ratio ( δ 18 O PO 4 ) is a useful technique to trace the sources and biogeochemical cycles of phosphorus (P) in aquatic ecosystems. However, δ 18 O PO 4 has not been widely used in oligotrophic freshwater systems due to technical and methodological difficulties in collecting sufficient phosphate (PO4 ) for the δ 18 O PO 4 analysis, which sometimes requires hundreds of liters of the water sample. In this study, a new approach (PaS‐Zir) was developed for the δ 18 O PO 4 analysis in oligotrophic freshwater systems using zirconium (Zr)‐loaded (ZrIRC) resin, which has a high affinity for PO4 . Methods: ZrClO2 was added to Amberlite IRC748 to obtain the ZrIRC resin. The adsorption/desorption experiment using KH2 PO4 with a known value of δ 18 O PO 4 was conducted to determine the adsorption/desorption properties of the resin and the likelihood of isotopic fractionation. By installing mesh bags filled with the resin, the PaS‐Zir approach was used in two rivers with low PO4 concentrations (0.2 and 5.3 μmol/L). A conventional sampling method was also performed in the study river with a higher PO4 concentration to validate the efficacy of the PaS‐Zir method. Results: The adsorption/desorption experiment demonstrated that the ZrIRC resin possessed a sufficient adsorption capacity (153 μmol/resin‐mL) and exhibited little isotopic fractionation during the adsorption/desorption processes. Using the PaS‐Zir method, we were able to collect sufficient PO4 samples for the δ 18 O PO 4 analysis from the rivers within at least 4 days of mesh bag installation. The δ 18 O PO 4 values (14.2‰ ± 0.2‰) obtained using the PaS‐Zir method were comparable to those obtained using the conventional method (14.0‰ ± 0.03‰). Conclusion: We proved that the PaS‐Zir method is applicable to oligotrophic freshwater systems and is generally more efficient than the conventional method. In addition, our method is useful for improving the understanding of the P dynamics of oligotrophic ecosystems because of the extremely low concentration of PO4 commonly found in them, which are often prone to P pollution.